INNOVATING TOURISM SERVICES: A KNOWLEDGE-BASED APPROACH TO IT INTEGRATION AND EXTERNAL COLLABORATION - Kuang Yu Chang,; Lin, Chen-Hsien (PEOPLE: International Journal of Social Sciences, 2025)
This study investigates the interplay between knowledge capabilities, dynamic capabilities, and service innovation within the travel agency sector. Specifically, it examines how knowledge aggregation and transformation contribute to the development of integrative dynamic capabilities and how these capabilities drive service innovation. The study further explores the moderating roles of IT integration capability and knowledge desorption, offering a nuanced understanding of their influence on the relationships between knowledge capabilities and service innovation. Grounded in the knowledge-based view (KBV) and dynamic capabilities theory (DCT), this research seeks to address existing gaps by constructing a comprehensive service innovation framework tailored to the travel industry.Empirical data were collected through a structured survey of travel agency managers, yielding 431 valid responses. Partial least squares structural equation modeling (PLS-SEM) was employed to validate the proposed model and test the hypothesized relationships. The results confirm that knowledge aggregation and transformation significantly enhance integrative dynamic capabilities, including both internal and external integration capabilities. Internal integrative capabilities, in particular, exhibit a direct and positive effect on service innovation, highlighting the critical role of internal coordination and resource alignment. Moreover, IT integration capability and knowledge desorption were found to moderate these relationships, emphasizing their strategic importance in leveraging knowledge for innovation.The findings provide valuable theoretical contributions by enriching KBV and DCT, offering insights into the mechanisms through which knowledge facilitates service innovation. Additionally, this study offers practical recommendations for travel agencies, emphasizing the importance of investing in IT systems and fostering knowledge-sharing practices with external partners to enhance service innovation outcomes. By linking knowledge and dynamic capabilities to service innovation, this research offers a robust foundation for improving organizational competitiveness in the dynamic tourism market.